Traditional Natural Colour of Assam (International Journal of Scientific Research and Management (IJSRM), 2017)
People in the past always created somethingnew tofulfil their need. The great Vaishnava saint of Assam, Sri Sankardevabelonged in 14th (fourteen) century believed that “Beauty is God”. Being a real artist he created some beautiful items BrindabaniBastra – A famous handloom textiles of the world in which life of Lord Krishna was depicted with prominent figure painted with artistic naturalcolour produced from plant source, mainly from bark, leaves, fruit, flower, roots etc. which was remain same till this century. At that period he created a special natural colour known as “Mohi” to write on Sanchipat and Hengulhaital colour for colouring of wooden instruments, walls, mukhasilpa, and boat. As it is considered as a the duty of young talents of our state to protect the uniqueness, greatness of SrimantaSankardeva’s creation , an attempt was made to find out the traditional mechanism of natural dye specially in his period. The study showed that the basic colour of that period were mohi(bluish green ink) yellow arsenic(haital),vermillion (hengul), in eco- friendly methods.